Contagem de reticulócitos de cães saudáveis ou anêmicos pela citometria de fluxo - Pereira, P. M.; Seki, M. C. [UNESP]; Palma, P. V. B.; Morais, F. R.; Santana, Áureo Evangelista [UNESP]; Pereira, G. T. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
Compararam-se os resultados da contagem de reticulócitos pela microscopia de luz e pelo método da citometria de fluxo em 25 cães saudáveis (controle), 60 cães com anemia regenerativa e 40 com anemia arregenerativa. Houve diferença nas contagens absolutas obtidas pela microscopia de luz e pela citometria de fluxo nos três grupos estudados. A contagem de reticulócitos foi mais alta pela citometria de fluxo que a contagem pela microscopia de luz, mostrando ser um método mais sensível, simples e seguro para a quantificação de reticulócitos.

Counts of reticulocytes using both the light microscopy and flow cytometry (FC) methods in 25 healthy control dogs, 60 dogs with regenerative anemia, and 40 dogs with non-regenerative anemia were compared. The absolute counts were submitted to the paired t-Student test, which determined significant differences (P<0.0001) between those methods in the three studied groups. Counts of retyculocytes were higher under flow cytometry, which proved to be a more sensitive method. Flow cytometry is a simple and reliable method for the quantification of reticulocytes.
Count of reticulocyte counts of healthy or anemic dogs by flow cytometry
Keywords: Dog; Flow cytometry; Anemia; reticulocyte; Cão; Citometria de fluxo; Anemia; reticulócitos